Mandar Culture-Based English Education - Rafiqa Rafiqa; Ahmad Munawir (ELT Worldwide: Journal of English Language Teaching, 2017)
The purpose of this article is to describe a model of English language learning based on Mandar culture. Descriptive method was used in this study, the aim of it to describe a contextual learning model so the students are able to speak English and still preserve Mandar culture. The purposive sampling technique was used to determine the sample of the research, all of the students of English Education Program in 2016 academic year. Data were collected by using observation technique, questionnaire and documentation. This study described about English language learning based on Mandar culture. It was a process of language learning combined with local culture, namely Mandar culture. This study incorporates elements of Mandar culture in the learning process with the aim that students can understand and preserve their own culture and can add their English vocabulary. There are six Mandar cultural themes in Mandar culture-based language learning, namely malatigi (Mandar customary ritual on the night of marriage), mandarese marriage, sayyang pattuddu ', sayyang-sayyang, fisherman party (Sandeq), and panette' (making Mandar silk sarong). Applying Mandar cultures in English language learning can improve English language students and the students can preserve Mandar culture and increase student interest and critical thinking skills.